Geomorphological Controls on Soil Fertility Across Potential Rice Expansion Areas in Tropical Lowlands - Bagus Adi Nugroho; Adiprasetya Widyatama; Halim Ma'shum; Bardhian Cahyo Aji Gumilang (Acta Solum, 2026)
Geomorphological variability strongly influences soil fertility conditions in tropical lowland environments and plays an important role in determining the potential for rice expansion. This study evaluated geomorphological controls on soil fertility across potential areas for rice expansion in Makroman, East Kalimantan, Indonesia, using a pedogeomorphic approach. Geomorphic units were delineated through visual interpretation of satellite imagery, field observations, and DEMNAS-derived elevation data. The study area was classified into four major geomorphic units: floodplains, undulating plains, rolling plains, and slopes. Soil fertility characteristics, including soil pH, soil organic carbon (SOC), and cation exchange capacity (CEC), were obtained from field-based soil observations and laboratory analyses across representative geomorphic units. The results revealed a clear fertility gradient across geomorphic units associated with dominant geomorphic processes. Floodplain environments exhibited the highest pH (5.8), SOC (1.7%), and CEC (32.4 cmol(+) kg⁻¹), whereas slopes showed lower pH (4.9), SOC (0.8%), and CEC (27.3 cmol(+) kg⁻¹). Intermediate conditions were observed in undulating and rolling plains, reflecting transitional redistribution and runoff-dominated processes. Depositional environments favored the accumulation of fine particles, organic matter, and exchangeable base cations, while erosional and leaching processes progressively reduced nutrient retention in elevated landscapes. These findings demonstrate that soil fertility variability in tropical lowlands is controlled not only by geomorphic position but also by the dominant geomorphic processes operating across the landscape. The study highlights the importance of geomorphology-based approaches for supporting sustainable rice expansion and land management in tropical agricultural environments.